Does religiosity affect financing activity? Evidence from Indonesia - Fatwa Wijaya, Ibrahim; Moro, Andrea; Belghitar, Yacine (Wiley, 2022)
We examine the role of religiosity on the financing activities in both Islamic and conventional banks in Indonesian provinces by using five different measures of religiosity: number of Islamic schools, hajj application, number of Islamic seminary schools, number of Mosques, and number of certified halal products. Based on regression analysis, the results show that both Islamic and conventional banks provide more financing in religious provinces. Religiosity also helps in reducing the volume of non-performing financing. Our the results are still qualitatively valid after taking into account endogeneity issue that emanates from omitted variables (i.e., unobservable beliefs, ideas, and attitudes), and possible reverse causality between religiosity and the total amount of financing at the province level.
Keywords: conventional bank; financing; Islamic bank; non-performing finance; religiosity